2017
DOI: 10.1189/jlb.3hi0517-198r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Proliferation of Ly6C+ monocytes during urinary tract infections is regulated by IL-6 trans-signaling

Abstract: Ly6C monocytes are important components of the innate immune defense against infections. These cells have been shown to proliferate in the bone marrow of mice with systemic infections. However, the proliferative capacity of Ly6C monocytes in infected peripheral tissues as well as the associated regulatory mechanisms remain unclear. In this study, we analyzed the proliferative capacity of Ly6C monocytes in the urinary bladder after infection with uropathogenic E. coli, one of the most prevalent pathogen worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
3
18
0
1
Order By: Relevance
“…In contrast to previous findings showing that mature MΦ proliferate, we found a significant percentage of inflammatory Ly6C+F4/80lo/− Mo/MΦ in the DNA synthesis and dividing phases of the cell cycle (S/G2/M) in response to injury, whereas mature MΦ (Ly6C−F4/80+) showed the opposite trend, with an increased percentage of cells in the resting G0 phase. Therefore, proliferation contributes to accumulation of Ly6C+F4/80lo/− Mo/MΦ in skin wound healing, similar to a recent study using an infection model, which detected higher proliferation of Ly6C+ Mo compared with Ly6C− MΦ in mouse bladder . In addition to proliferation, other factors such as rates of cell infiltration, Mo differentiation, cell efflux, and apoptosis may also contribute to Mo/MΦ accumulation in wounds.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast to previous findings showing that mature MΦ proliferate, we found a significant percentage of inflammatory Ly6C+F4/80lo/− Mo/MΦ in the DNA synthesis and dividing phases of the cell cycle (S/G2/M) in response to injury, whereas mature MΦ (Ly6C−F4/80+) showed the opposite trend, with an increased percentage of cells in the resting G0 phase. Therefore, proliferation contributes to accumulation of Ly6C+F4/80lo/− Mo/MΦ in skin wound healing, similar to a recent study using an infection model, which detected higher proliferation of Ly6C+ Mo compared with Ly6C− MΦ in mouse bladder . In addition to proliferation, other factors such as rates of cell infiltration, Mo differentiation, cell efflux, and apoptosis may also contribute to Mo/MΦ accumulation in wounds.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, we hypothesized that changes in the microenvironment of these cells as they infiltrate wounds drives Mo/MΦ into the proliferative phases of the cell cycle. Several cytokines can promote Mo/MΦ lineage cell proliferation in different tissues, thus we assessed the potential roles of M‐CSF, IL‐4, IL‐1β, and IL‐6 on Mo/MΦ proliferation in skin wounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…show that Ly6C‐expressing myeloid cells recruited to the site of an excisional skin wound undergo extensive proliferation 6 . These findings complement two recent studies that found urinary tract 7 and hepatic 8 monocytes to proliferate during bacterial and helminth infection, respectively, suggesting bone marrow‐derived monocytes are able to proliferate to a significant degree within certain inflamed tissues. Critically, Pang et al.…”
Section: Figuresupporting
confidence: 88%
“…28,29 These clinical associations are in line with results from functional studies that support a broadly pro-inflammatory role of IL-6 in asthma. For example, IL-6 has been shown to promote (1) the differentiation of T helper (Th) 2 over Th1 30,31 and Th17 over Treg cells 32,33 ; (2) mucus production 34 ; (3) immune cell recruitment, activation, proliferation and survival [35][36][37] ; (4) obesity-associated 38 and LPS-induced 39 inflammation. Most of these pro-inflammatory effects of IL-6 have been suggested to be mediated by the trans-signalling pathway.…”
Section: Introductionmentioning
confidence: 99%